2018
DOI: 10.5799/jmid.393890
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Methicillin-Resistant Staphylococcus aureus Isolate from Healthcare Workers in Larestan, Iran

Abstract: Objective: The aim of this study was to determine the antimicrobial susceptibility and cassette chromosome typing in Methicillin-Resistant Staphylococcus aureus (MRSA) isolated from healthcare workers. Methods:Two hundred thirty nasal swabs were collected from healthcare workers of three hospitals in Larestan, Iran. Antibiotic susceptibility was determined by disk diffusion method according to CLSI guideline. The minimum Inhibitory concentration (MIC) of vancomycin and screening test with methicillin were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Furthermore, studies have shown that most CA-MRSA isolates carry SCCmec types IV [24] and V [25] . In line with the present study results, Ebadi and Khaliliazad (2017) in their study in Larestan reported that type I (32.1%), type IV (28.6%), type V (14.3%), and type III (7.1%) were the most predominant SCCmec types, respectively [26] . However, in another study by Havaei et al (2017), CA-MRSA isolates harbored SCCmec type IV, while HA-MRSA isolates harbored type I (22.2%) and type III (2.2%) [27] .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, studies have shown that most CA-MRSA isolates carry SCCmec types IV [24] and V [25] . In line with the present study results, Ebadi and Khaliliazad (2017) in their study in Larestan reported that type I (32.1%), type IV (28.6%), type V (14.3%), and type III (7.1%) were the most predominant SCCmec types, respectively [26] . However, in another study by Havaei et al (2017), CA-MRSA isolates harbored SCCmec type IV, while HA-MRSA isolates harbored type I (22.2%) and type III (2.2%) [27] .…”
Section: Discussionsupporting
confidence: 91%
“…There are several factors that affect the frequency of MRSA strains, particularly among patients and in different geographic areas (19,20). Methicillin-resistant S. aureus screening revealed prevalence of 87.9%.…”
Section: Discussionmentioning
confidence: 99%